ANALYSIS OF THE PRACTICE OF RICE SHARING COOPERATION FROM THE PERSPECTIVE OF AKAD MUZARA’AH - M Rivaldi; Abd Razak (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
The agricultural sector plays a vital role in supporting the community, not only as a source of income but also as a central pillar of national food security. In Indonesia, particularly in Gampong Lhok Dalam, Peureulak Timur Subdistrict, East Aceh Regency, the profit-sharing cooperation pattern between landowners and farmers has long been a traditional practice. This study aims to examine the rice farming profit-sharing system in the village from the perspective of muzara’ah contracts and Islamic economic law. The study uses a descriptive qualitative approach, with data collected through interviews with landowners and farmers, accompanied by a review of relevant literature. Findings in the field indicate that profit-sharing cooperation is still conducted verbally, without a written agreement. The pattern of profit sharing also varies—generally 1:2 or 1:3—depending on the agreement and each party’s contributions. In many cases, the cultivators bear all production costs, such as seeds, fertilisers, and labour, but receive a smaller share of the profits than the landowners. This condition indicates an imbalance that does not reflect the principle of fairness in muzara‘ah contracts. This study also found a lack of transparency in the crop yield recording process, which often leads to disputes between the cooperating parties. From the perspective of Islamic economic law, this practice is not fully compliant with sharia provisions because it still contains elements of gharar (uncertainty) and the potential for actions that are detrimental to one party (zulm). Therefore, it is necessary to understand and apply the muzara’ah contract more formally through clear, written, and transparent agreements so that the division of rights and obligations can be carried out fairly in accordance with sharia principles. The results of this study are expected to form the basis for developing a sharia-based agricultural cooperation model that can improve farmers’ welfare and sustainably strengthen the village economy.